2020
DOI: 10.1371/journal.pone.0227291
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis recurrences and predictive factors in a vulnerable population in Catalonia

Abstract: Background Patients with a history of tuberculosis (TB) have a high probability of recurrence because long-term cure is not always maintained in successfully treated patients. The aim of this study was to identify the probability of TB recurrence and its predictive factors in a cohort of socially vulnerable patients who completed treatment in the TB referral center in Catalonia, which acts as the center for patients with social and health problems. Methods This retrospective open cohort study included all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…36 However, a recent study in Spain showed that smoking was not a predictive factor for recurrence. 39 Exact reasons of these homogeneous results need to be further studied, and could be to the different definitions of smoking status used. In contrary to our study, the definition used in the Spain study was persons who smoke any number of cigarettes every day during the past month.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, a recent study in Spain showed that smoking was not a predictive factor for recurrence. 39 Exact reasons of these homogeneous results need to be further studied, and could be to the different definitions of smoking status used. In contrary to our study, the definition used in the Spain study was persons who smoke any number of cigarettes every day during the past month.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence of TB following successful treatment is considered one of the main challenges posed to TB control in many countries. It is evident that even after successfully treating this infectious disease, individuals with a previous history of TB infection are at a higher risk of recurrent TB [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Moreover, the rate of TB recurrence differs widely among countries and regions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the TB burden declined in recent years before the COVID-19 pandemic [ 3 ], it is a disease difficult to control and eliminate due to co-infection with human immunodeficiency virus (HIV); antimicrobial resistance; multidrug-resistant TB; and increased consumption of alcohol, tobacco, and/or other drugs. In addition, TB is associated with social determinants of health, such as social vulnerability, poverty, and social exclusion to which populations such as immigrants, refugees, the homeless, and the incarcerated population are exposed [ 4 ]. It is estimated that 90% of the patients diagnosed with TB live in vulnerable environments with limited health resources [ 5 ], such as individuals living in correctional facilities.…”
Section: Introductionmentioning
confidence: 99%